The role of means of communication in changing the attitudes of Palestinian youth A Field Study on a Sample of University Students in the West Bank - Elian, Emran Ali (Journal of Humanities & Social Sciences, 2020)
This study aims to identify the role of the means of communication by changing social, cultural, economic and political trends ,from the viewpoint of Palestinian university students in west bank, in the light of some demographic variables, and to achieve the objectives of the study were used descriptive and analytical approach, the study sample consisted which was the analysis of the data from the (168) students , they applied a questionnaire consisted of (28) items, divided into four main areas. The study concluded that a set of results, including: that the role of the means of communication in changing social trends came by (88.96%), and was the area of ​​change in the social sphere in the first place with a relative weight reached (96%), followed by a change in the cultural field relative weight was ( 91.06%), then the economic sphere relative weight was (89.90%), and was the last level the political field by (82.90%). and it found that there were no statistically significant differences between the averages of students’ estimates of the role of the means of communication in changing social attitudes attributed to the variables of age, sex, social status, and academic level. In light of the results of the study the researcher recommended the need to encourage dialogue; to increase awareness to achieve positive change through media and advertising campaigns, and the importance of university curricula included topics about youth participation in political programs, economic, and social and cultural to bring about positive change.